A film-coated iron adhesion detection method and detection device
Patent Information
- Application Number
- CN202611295268.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-13
AI Technical Summary
[0003]现有技术存在以下共性缺陷:常规附着力测试方法在常温常压下进行,无法模拟高温高压蒸汽的实际使用环境,测试结果与实际工况相关性不足;耐蒸煮测试仅进行目视外观检查或蒸煮后定性复测,缺乏对附着力的定量评价手段,无法对不同覆膜铁产品或工艺进行精确的附着力水平对比;对于双面覆膜铁,现有技术缺乏针对单一面附着力进行独立评价的标准化样品处理方案
本申请结构紧凑、合理,操作方便,在加压高温蒸汽杀菌处理过程中对样品同步施加恒定机械载荷,使薄膜-基板界面同时承受高温下薄膜与金属基板热膨胀系数差异导致的界面热应力、水蒸汽渗透应力、持续机械应力的耦合作用;三重应力的同步叠加精确模拟了覆膜铁在实际蒸煮杀菌过程中所经历的多因素协同失效机制,能够模拟覆膜铁样品实际蒸煮使用工况。
Smart Images

Figure CN122901073A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of metal packaging material testing technology, and in particular to a method and device for testing the adhesion of coated iron. Background Technology
[0002] Coated steel is a functional composite material formed by bonding a polymer film to the surface of a metal substrate through a thermal bonding process. It is widely used in food cans, beverage cans, chemical packaging containers, and other fields. The interfacial bonding force between the film and the metal substrate in coated steel is a key performance indicator that determines the sealing performance, corrosion resistance, and service life of the packaging container. In actual use, food and beverage packaging containers need to undergo high-temperature sterilization at 121–135°C. During this process, the film-metal substrate interface is simultaneously subjected to the coupled effects of thermal stress, water vapor permeation stress, and mechanical stress, which is the root cause of blistering, delamination, and peeling failures of the coated steel film during sterilization.
[0003] Existing technologies have the following common defects: conventional adhesion testing methods are conducted at room temperature and pressure, which cannot simulate the actual use environment of high temperature and high pressure steam, and the test results are not sufficiently correlated with actual working conditions; the boiling resistance test only conducts visual inspection or qualitative retest after boiling, lacking quantitative evaluation methods for adhesion, and cannot accurately compare the adhesion levels of different coated iron products or processes; for double-sided coated iron, existing technologies lack standardized sample processing schemes for independent evaluation of adhesion on a single side.
[0004] Therefore, there is an urgent need in this field for a method and supporting device for testing the adhesion of coated iron that can simulate the multi-stress coupling state in actual cooking conditions, achieve quantitative evaluation of adhesion, and have a high correlation between test results and actual performance.
[0005] Therefore, we propose a method and device for testing the adhesion of coated iron. Summary of the Invention
[0006] To address the shortcomings of existing production technologies, the applicant provides a method and apparatus for testing the adhesion of coated iron. This method applies a constant mechanical load to the sample simultaneously during pressurized high-temperature steam sterilization, causing the film-substrate interface to simultaneously bear the coupling effects of interfacial thermal stress, water vapor permeation stress, and continuous mechanical stress caused by the difference in thermal expansion coefficients between the film and the metal substrate at high temperatures. This method can simulate the actual steaming and cooking conditions of coated iron samples.
[0007] The technical solution adopted in this application is as follows: A method for testing the adhesion of coated iron includes the following steps: S1. Cut the coated iron sample to form a cut on the coated iron sample, so that the non-test surface film is separated from the metal substrate, while the test surface film remains on the surface of the metal substrate. S2. Fold the treated coated iron sample to form a hanging structure, and form through holes at the preset positions of the coated iron sample. S3. Connect a weight of a preset weight to the coated iron sample through the through hole of the coated iron sample, and fix the coated iron sample with the weight suspended on the base. S4. Place the coated iron sample fixed to the base, along with the weights, into a pressurized high-temperature steam environment for sterilization. S5. After the sterilization treatment is completed, take out the coated iron sample, measure the peel length of the film on the test surface, and evaluate the adhesion performance of the coated iron sample based on the peel length.
[0008] Its further features are: In step S4, the sterilization temperature is 121℃-130℃, and the treatment time is 15 minutes-60 minutes.
[0009] In step S4, the steam pressure for sterilization is 0.2 MPa-0.27 MPa.
[0010] In step S3, the weight of the weight is 50g-200g.
[0011] In step S1, the length of the cut coated iron sample is 80mm-150mm, the width is 25mm-50mm, the cut depth of the coated iron sample is 0.1mm-0.5mm, and the cut is formed along the width direction of the coated iron sample.
[0012] In step S5, the peel length is measured as follows: at least 5 equally spaced positions are selected in the width direction of the coated iron sample, and the peel length of the film at each position is measured. The arithmetic mean is taken as the final peel length result.
[0013] In step S5, the peeling length is measured using a measuring tool with an accuracy of not less than 0.5 mm.
[0014] This application also discloses a device for testing the adhesion of coated iron, comprising: The base is used to fix the coated iron sample. The base is made of high temperature and corrosion resistant material and can be placed entirely into a pressure sterilization container. The sample clamping structure, set on the base, is used to clamp and fix the coated iron sample; Weights, detachably connected to the coated iron sample, are used to apply a constant gravitational load to the coated iron sample.
[0015] The base is provided with a marking area for marking the coated iron sample.
[0016] The base is a rectangular plate structure made of stainless steel.
[0017] The beneficial effects of this application are as follows: This application features a compact and reasonable structure and is easy to operate. During the pressurized high-temperature steam sterilization process, a constant mechanical load is applied to the sample simultaneously, so that the film-substrate interface is simultaneously subjected to the coupling effect of interfacial thermal stress, water vapor permeation stress and continuous mechanical stress caused by the difference in thermal expansion coefficients between the film and the metal substrate at high temperature. The synchronous superposition of the triple stress accurately simulates the multi-factor synergistic failure mechanism experienced by the coated iron in the actual cooking sterilization process, and can simulate the actual cooking and use conditions of the coated iron sample.
[0018] In addition, this application also has the following advantages: (1) Using the film peel length as a quantitative evaluation index of adhesion, and in conjunction with a standardized measurement scheme that selects at least 5 equally spaced positions in the width direction of the coated iron sample for multi-point measurement and takes the arithmetic mean, the adhesion of the coated iron sample is accurately quantitatively evaluated. It can accurately distinguish the subtle differences in adhesion between different batches and different processes of coated iron samples, and is suitable for the refined control of product quality.
[0019] (2) The non-test surface film of the coated iron sample is separated from the metal substrate by cutting, while the test surface film is completely preserved. This allows for independent adhesion evaluation of any side of the double-sided coated iron sample, solving the problem that the adhesion of a single side of the double-sided coated iron sample cannot be evaluated separately in the prior art. Attached Figure Description
[0020] Figure 1 This is a flowchart illustrating the process of this application.
[0021] Figure 2 This is a schematic diagram of the coated iron sample of this application.
[0022] Figure 3 This is a schematic diagram of the coated iron sample after folding and punching according to this application.
[0023] Figure 4 This is a schematic diagram of the coated iron sample of this application after suspending weights.
[0024] Figure 5 This is a schematic diagram of the coated iron sample of this application fixed on the base after being suspended by weights. Detailed Implementation
[0025] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, the specific embodiments of this application are described in detail below with reference to the accompanying drawings. Many specific details are set forth in the following description to provide a thorough understanding of this application. However, this application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of this application. Therefore, this application is not limited to the specific embodiments disclosed below.
[0026] In the description of this application, it should be understood that if terms such as "center", "longitudinal", "lateral", "length", "width", "thickness", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", "counterclockwise", "axial", "radial", "circumferential" appear, these terms indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, and are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this application.
[0027] Furthermore, where the terms "first" and "second" appear, these terms are for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined with "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, where the term "multiple" appears, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0028] In this application, unless otherwise expressly specified and limited, the terms "installation," "connection," "joining," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components, unless otherwise expressly limited. Those skilled in the art can understand the specific meaning of the above terms in this application based on the specific circumstances.
[0029] In this application, unless otherwise expressly specified and limited, the use of descriptions such as "above" or "below" the second feature indicates that the first and second features are in direct contact or indirect contact via an intermediate medium. Furthermore, "above," "on top of," and "over" the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. Similarly, "below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.
[0030] It should be noted that if an element is referred to as being "fixed to" or "set on" another element, it can be directly on the other element or there may be an intervening element. If an element is considered to be "connected to" another element, it can be directly connected to the other element or there may be an intervening element. If so, the terms "vertical," "horizontal," "upper," "lower," "left," "right," and similar expressions used in this application are for illustrative purposes only and do not represent the only possible implementation.
[0031] like Figures 1-5 As shown, a method for testing the adhesion of coated iron includes the following steps: S1. Cut the coated iron sample to form a cut on the coated iron sample, so that the non-test surface film is separated from the metal substrate, while the test surface film remains on the surface of the metal substrate. S2. Fold the treated coated iron sample to form a hanging structure, and form through holes at the preset positions of the coated iron sample. S3. Connect a weight of preset weight to the coated iron sample through the through hole of the coated iron sample, and fix the coated iron sample with the weight suspended on the base. S4. Place the coated iron sample fixed to the base, along with the weights, into a pressurized high-temperature steam environment for sterilization. S5. After the sterilization treatment is completed, take out the coated iron sample, measure the peel length of the film on the test surface, and evaluate the adhesion performance of the coated iron sample based on the peel length.
[0032] In step S4, the sterilization temperature is 121℃-130℃, and the treatment time is 15 minutes-60 minutes.
[0033] In step S4, the steam pressure for sterilization is 0.2 MPa-0.27 MPa.
[0034] In step S3, the weight of the weight is 50g-200g.
[0035] In step S1, the length of the cut coated iron sample is 80mm-150mm, the width is 25mm-50mm, the cut depth of the coated iron sample is 0.1mm-0.5mm, and the cut is formed along the width direction of the coated iron sample.
[0036] In step S5, the peel length is measured as follows: at least 5 equally spaced positions are selected in the width direction of the coated iron sample, and the peel length of the film at each position is measured. The arithmetic mean is taken as the final peel length result.
[0037] In step S5, the peeling length is measured using a measuring tool with an accuracy of not less than 0.5 mm.
[0038] A device for testing the adhesion of coated iron, used in the aforementioned method for testing the adhesion of coated iron, comprising: The base is used to fix the coated iron sample. The base is made of high temperature and corrosion resistant material and can be placed entirely into a pressure sterilization container. The sample clamping structure, set on the base, is used to clamp and fix the coated iron sample; Weights, detachably connected to the coated iron sample, are used to apply a constant gravitational load to the coated iron sample.
[0039] The base has a marking area for marking the coated iron samples.
[0040] The base is a rectangular plate structure made of stainless steel.
[0041] Example 1 Select a coated iron sample with a thickness of 0.20 mm and perform adhesion testing according to the following steps: S1. Cut the coated iron sample into a rectangle with a length of 120mm and a width of 30mm. Make a cut with a depth of about 0.18mm along the width direction at one end of the cut coated iron sample. Use a knife to separate and remove the non-test surface film from the metal substrate along the cut, leaving the test surface film intact. S2. Fold the coated iron sample 180° about 15mm from the top along the length of the sample, so that the folded coated iron sample forms an inverted L-shaped hanging structure. Punch a 5mm diameter through hole at the top of the folded coated iron sample about 8mm from the edge. S3. Insert the hook through the through hole, and suspend a 100g standard weight at the lower end of the hook. Fix the coated iron sample with the suspended weight on the base so that the coated iron sample is suspended vertically and the weight hangs down naturally to apply a constant gravity load. S4. Place the entire base containing the coated iron sample into a laboratory pressure sterilizer and sterilize it for 25 minutes at 125°C and 0.23 MPa steam pressure. S5. After sterilization, remove the coated iron sample and allow it to cool naturally to room temperature. Observe the peeling of the film on the test surface. Use a vernier caliper with an accuracy of 0.5 mm to measure the peeling length of the film at 5 equally spaced positions in the width direction of the coated iron sample.
[0042] During the pressurized high-temperature steam sterilization process, a constant mechanical load is applied to the sample simultaneously, so that the film-substrate interface is simultaneously subjected to the coupling effect of interfacial thermal stress, water vapor permeation stress and continuous mechanical stress caused by the difference in thermal expansion coefficients between the film and the metal substrate at high temperature. The simultaneous superposition of the triple stress accurately simulates the multi-factor synergistic failure mechanism experienced by the coated iron in the actual cooking sterilization process, and can simulate the actual cooking and use conditions of the coated iron sample.
[0043] Using the film peel length as a quantitative evaluation index of adhesion, and in conjunction with a standardized measurement scheme that involves selecting at least 5 equally spaced locations along the width of the coated iron sample for multi-point measurement and taking the arithmetic mean, a precise quantitative evaluation of the adhesion of coated iron samples is achieved. This scheme can accurately distinguish subtle differences in adhesion between coated iron samples from different batches and with different processes, and is suitable for refined control of product quality.
[0044] By cutting the coated iron sample, the non-test surface film is separated from the metal substrate, while the test surface film is completely preserved. This allows for independent adhesion evaluation of either side of the double-sided coated iron sample, solving the problem in the prior art that the adhesion of a single side of the double-sided coated iron sample cannot be evaluated independently.
[0045] The above description is an explanation of this application and not a limitation thereof. The scope of this application is defined by the claims. Within the scope of protection of this application, any form of modification may be made.
Claims
1. A method for testing the adhesion of coated iron, characterized in that, Includes the following steps: S1. Cut the coated iron sample to form a cut on the coated iron sample, so that the non-test surface film is separated from the metal substrate, while the test surface film remains on the surface of the metal substrate. S2. Fold the treated coated iron sample to form a hanging structure, and form through holes at the preset positions of the coated iron sample. S3. Connect a weight of preset weight to the coated iron sample through the through hole of the coated iron sample, and fix the coated iron sample with the weight suspended on the base. S4. Place the coated iron sample fixed to the base, along with the weights, into a pressurized high-temperature steam environment for sterilization. S5. After the sterilization treatment is completed, take out the coated iron sample, measure the peel length of the film on the test surface, and evaluate the adhesion performance of the coated iron sample based on the peel length.
2. The method for detecting the adhesion of coated iron as described in claim 1, characterized in that: In step S4, the sterilization temperature is 121℃-130℃, and the treatment time is 15 minutes-60 minutes.
3. The method for detecting the adhesion of coated iron as described in claim 1, characterized in that: In step S4, the steam pressure for sterilization is 0.2 MPa-0.27 MPa.
4. The method for detecting the adhesion of coated iron as described in claim 1, characterized in that: In step S3, the weight of the weight is 50g-200g.
5. The method for testing the adhesion of coated iron as described in claim 1, characterized in that: In step S1, the length of the cut coated iron sample is 80mm-150mm, the width is 25mm-50mm, the cut depth of the coated iron sample is 0.1mm-0.5mm, and the cut is formed along the width direction of the coated iron sample.
6. The method for testing the adhesion of coated iron as described in claim 1, characterized in that: In step S5, the peel length is measured as follows: at least 5 equally spaced positions are selected in the width direction of the coated iron sample, and the peel length of the film at each position is measured. The arithmetic mean is taken as the final peel length result.
7. The method for testing the adhesion of coated iron as described in claim 1, characterized in that: In step S5, the peeling length is measured using a measuring tool with an accuracy of not less than 0.5 mm.
8. A device for testing the adhesion of coated iron, used to implement the method for testing the adhesion of coated iron according to any one of claims 1-7, characterized in that, include: The base is used to fix the coated iron sample. The base is made of high temperature and corrosion resistant material and can be placed entirely into a pressure sterilization container. The sample clamping structure, set on the base, is used to clamp and fix the coated iron sample; Weights, detachably connected to the coated iron sample, are used to apply a constant gravitational load to the coated iron sample.
9. The coating adhesion testing device as described in claim 8, characterized in that: The base is provided with a marking area for marking the coated iron sample.
10. The coating adhesion testing device as described in claim 9, characterized in that: The base is a rectangular plate structure made of stainless steel.